Numerical investigation on micro-bending and springback with improved surface layer model. (1st January 2012) - Xu, Zhenying; Wang, Yun; Ding, Sheng; Wang, Rongmao; Dong, Peilong
Surface layer model can explain the first order size effect, but it is difficult to solve the micro-bending and springback due to the size effect. So the improved surface layer model was proposed based on the constitutive model considering the first order size effect. It consists of upper surface layer, upper transition layer, inner layer, bottom transition layer and bottom surface layer. And the micro V-bending geometry model was developed using analysis method. Combined with the dynamic explicit and static implicit codes, the corresponding finite element model was established in ABAQUS to simulate the micro V-bending and springback of H62 ultra-thin sheet. The comparison between the improved model and traditional model showed that it is more accurate for the forming force, stress changes and residual stress with improved model. The improved surface model can be better used into the micro-forming investigation.